Diacetylcurcumin: a novel strategy against Enterococcus faecalis biofilm in root canal disinfection - Souza, Vanessa de; Polaquini, Carlos Roberto [UNESP]; Moraes, Graciele Ribeiro de [UNESP]; Braga, Arthur Rodrigues Oliveira; Silva, Priscila Vieira da; Silva, Diego Romario da; Lima, Francisco Ricardo Ribeiro; Regasini, Luis Octavio [UNESP]; Cassia Orlandi Sardi, Janaina de (Taylor & Francis Ltd, 2024)
Aim: We evaluated Diacetylcurcumin (DAC), a derivative of curcumin, for its antibacterial and antibiofilm properties against Enterococcus faecalis. Methods: Minimum inhibitory concentration (MIC) and minimum bactericidal concentration were determined, along with antibiofilm potential and toxicity in Galleria mellonella. Additionally, in silico computational analysis was performed to understand its mechanisms of action. Results & conclusion: DAC demonstrated significant antibacterial effects, with MIC and MBC values of 15.6 and 31.25 mu g/ml, respectively, and reduced biofilm formation. A synergistic effect, reducing biofilm by 77%, was observed when combined with calcium hydroxide. G. mellonella toxicity tests confirmed DAC's safety at tested concentrations, suggesting its potential for use in root canal disinfection products.
Keywords: antimicrobial; biofilm; curcuminoid; Enterococcus faecalis; root canal